Comparison of stationary and dynamic fractional CO2 laser modalities of large burns treatment: Experimental laboratory model. Issue 1 (February 2023) - Haik, Josef; Segalovich, Matan; Visentin, Denis; Lepselter, Josef; Cleary, Michelle; Kornhaber, Rachel; Harats, Moti
Highlights: Large burn scars present complex procedural challenges for burn clinicians. Fractional ablative and non-ablative lasers are an adjunct treatment for burn scars. We present a non-clinical model on the practicality of dynamic and stationary CO2 fractional laser. Abstract: Objectives: To experimentally compare two fractional ablative CO2 laser handpieces intended for the treatment of large area burn scars. Each handpiece coverage rate, depth of penetration and application time were measured and compared in a simulation model of large area burns scars using a dynamic/roller handpiece (small footprint) and a stationary/stamping handpiece (large footprint). Methods: A 30 W fractional ablative CO2 laser was applied using 2 different handpieces and footprints on a A4 size paper stack. The handpieces were a stationary (stamping) handpiece with 7 × 7 (49 pixels/square shape) and dynamic (roller) handpiece with 7 × 1 (7 pixels/single row shape). For both handpieces the laser settings were fixed at "High" power (30 W), providing an energy level of 100 mJ/pixel. Both handpieces were applied perpendicular to the surface, with the process repeated for the dynamic handpiece with an angled operation. The depth of laser penetration was assessed by the number of pages of paper having visible holes and burn area coverage time measured under each handpiece/condition. Results: The application time was faster and the penetration deeper for the dynamic handpiece compared to the stationary handpiece in both the perpendicular and angled conditions. This study has practical implications for lasers operators to improve time efficacy in large area scars with improved clinical endpoints. Conclusion: The fractional ablative dynamic handpiece demonstrated superior application efficiency compared to the stationary handpiece in the simulated treatment of large surface area burn scars, reducing treatment time with improved depth of penetration.